Sistem Informasi Angka Kesehatan Masyarakat Pada Puskesmas Sumberharta Berbasis Web Mobile - Ahmad Sobri (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2018)
-In writing this scientific paper the author will explain about the design of Information Systems Public Health Score On Puskesmas Resources Mobile Web-based Treasures using PHP programming materials (Hypertext Preprocessor), Jquery Mobile. Needs required in an Information System development that is using UML (Unified Modeling Language), Database created using MySQL. The results of this application development include Patient data, Disease data, Regional data and Transacation data. Based on the results of this study can be concluded that the software that is built is Data Processor Applications Community-based Web Health Benefits. The results of this application is expected to provide convenience in processing / processing data into information fast, precise, accurate and certainly useful for all parties.